Enhancement of the strength-ductility relationship for carbon nanotube/Al–Cu–Mg nanocomposites by material parameter optimisation. (February 2020) - Liu, Z.Y.; Ma, K.; Fan, G.H.; Zhao, K.; Zhang, J.F.; Xiao, B.L.; Ma, Z.Y.
Abstract: Heterogeneous carbon nanotube (CNT)/Al–Cu–Mg composites, consisting of CNT-free coarse grain (CG) bands and CNT-rich ultrafine grain (UFG) zones, were fabricated to significantly enhance their strength-ductility. Their mechanical behavior as well as extra-strengthening and elongation increase mechanisms were investigated in detail, with the help of high-resolution digital image correlation (DIC) and extended finite element method (XFEM). A narrow CG band and medium CG content were found to be beneficial in increasing the strength-ductility. Under optimized conditions, a heterogeneous 3 vol% CNT/Al composite exhibited more than 100% elongation increase with nearly no ultimate tensile strength loss as compared to the uniform composite. Geometrically necessary dislocations were induced between the CG and UFG zones, leading to extra-strengthening beyond the rule-of-mixtures. Local strain and micro-crack propagation analyses based on DIC and XFEM indicated that strain localization was greatly suppressed and micro-cracks were effectively blunted because of the existence of CG bands, leading to considerably enhanced elongation. Finally, a model was proposed to assist the selection of the heterogeneous structure parameters for the strength-ductility design of the nanocomposite. The calculated safety zones for CG parameter selection were in well agreement with the experimental results. Graphical abstract: Image 1